(untitled) (Scientific journal of the Fergana State University, 2023)
Alginates are natural biopolymers found in algae, some bacteria and mosses. Their derivatives are used as hydrocolloids, emulsifiers in the food, pharmaceutical, textile and cosmetic industries, in dentistry for the manufacture of molds, as well as in various fields, such as wastewater treatment. This review presents natural sources and applications of alginates, extraction methods from algae using simple extraction methods and ultrasonic extraction, physico-chemical research methods (UV, IR, XRD), composition and structure analysis, reactivity, Gaussian 09 and Pass on-line results the results of theoretical analysis obtained using